1970
DOI: 10.3126/narj.v7i0.1862
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Vaireties of Onion and their Transplanting Times for Off-season Production in Mid Hills of Nepal

Abstract: A field experiment was conducted at the agro-ecological research site (AER site) of the RegionalAgriculture Regional Station, Lumle, at Deurali in Palpa (1200 masl) during rainy season of2004 and 2005. The main objective of the experiment was to evaluate the different varieties ofonion and their transplanting time for off-season production in mid hill conditions. Treatmentswere four onion varieties, namely LR-241, N-53, Nasik Red and Red Creole and four transplantingdates as 25 July, 5 August, 15 August, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The highest mean polar diameter (39.52 mm) was found on Puttarasal local and lowest (13.47 mm) was found on Nayagarh local 01. These results are in agreement with the results of the study conducted by Gautam et al, (2006) and Azoom et al, (2014). The lowest average equatorial diameter of 20.63 mm was recorded in Coimbatore Local White (Aca1) and highest equatorial diameter of 42.06 mm was found on Aca 15 (Puttarsal local).…”
Section: Growth Yield and Quality Characterssupporting
confidence: 83%
“…The highest mean polar diameter (39.52 mm) was found on Puttarasal local and lowest (13.47 mm) was found on Nayagarh local 01. These results are in agreement with the results of the study conducted by Gautam et al, (2006) and Azoom et al, (2014). The lowest average equatorial diameter of 20.63 mm was recorded in Coimbatore Local White (Aca1) and highest equatorial diameter of 42.06 mm was found on Aca 15 (Puttarsal local).…”
Section: Growth Yield and Quality Characterssupporting
confidence: 83%
“…Neck diameter (thickness) in onion is an important character, because it indicates bulb storage ability. The onion with thin neck diameter, store better than thick diameter 32 . The increase in neck diameter might show its involvement in the synthesis of amino acids, as they link together and form proteins and make up metabolic processes required for plant growth including neck thickening.…”
Section: Resultsmentioning
confidence: 97%
“…Neck thickness is an important trait of bulb quality in onion due to its effect on bulb storage ability. The onion with thin neck diameter stores better than one with thick diameter (Gautam et al, 2006). All the weed control treatments resulted in significantly higher bulb TSS than the weedy check.…”
Section: Weeds Density and Dry Weightmentioning
confidence: 86%
“…Moreover the produced bulbs at this date had the highest neck thickness (Table 5). Gautam et al (2006) reported that there were no significant differences for length and diameter of onion bulbs at different planting dates in summer. In this study, the highest percentage of bulb TSS was observed at last date of transplanting (Table 5).…”
Section: Weeds Density and Dry Weightmentioning
confidence: 97%